Evaluasi Pengembangan Keprofesian Berkelanjutan (PKB) Bidang Pengembangan Diri Guru di Gugus 3 Ciomas, Kabupaten Bogor - Luciana Gustina Tampubolon; Neti Karnati; Sugiarto (Program Studi Manajemen Pendidikan, 2023)
To improve professionalism, a teacher is obligated to develop himself. Teacher's self-development can be done by participating in the Continuing Professional Development (CPD) program. The purpose of CPD program is to improve teachers' competences and as a mean for their career development. The evaluation of the CPD program is very important to be carried out in order to measure the level of achievement and to provide supporting information for further decision making to maximize the program. The purpose of this study is to analyze the evaluation of the CPD program in the field of self-development which emphasizes on the final recommendation confirming that an object can be maintained, improved, repaired or even terminated in line with the data that has been obtained. This research method is an evaluative research with a discrepancy evaluation model. The results showed that self-development activities have a positive influence, especially in learning activities. However, there are still gaps in each stage of design, installation, process, product and comparison. Therefore, the self-development field in the CPD program must be improved by doing adjustments in each of the existing gaps.